(untitled) (European Journal of Behavioral Sciences, 2019)
The expediency of the organization of students’ studying and research activities from the perspective of a cognitive approach by methods of pedagogical intellectics is grounded. The logic of learning component-wise design is described (using didactic examples), the prototype of which is solving the problem of extracting expert knowledge. The content and features of the implementation of the author’s technique of rational organizing students’ studying and research activities on the basis of didactic concepts’ design are revealed. It is confirmed that the pedagogical intellectics is a solution of transferring the pedagogical potential of the individual from the existence to the development.